Training On Implementation of Early Childhood Education Curriculum 2013 and Assessment Record to Increase Teachers Competence - Sujana, Yudianto; Ramli, Murni; *, Suciati; Kurniawati, Dyah Yuni (Proceeding of International Conference on Teacher Training and Education, 2016)
Early childhood education (ECE) Curriculum 2013 has been socialized since 2014, and had been prior testedin some kindergarten Pembina. Other early childhood institutions must use the curriculum 2013 started in oddsemester of 2015. Early childhood education Curriculum 2013 focuses on scientific approaches and authenticassessment, in order to give children more space and challenge to freely develop their potential. In the processof implementation, many early childhood education teachers face difficulties in interpreting the needs of thenew curriculum, especially on how to conduct activities based on scientific approach, and assess childrendevelopment authentically. This fact occurs might be because of the socialization and training of theCurriculum 2013 were only theoretical based, rather than provide more practices to the participants. To solvethese problems, the Center for Japanese Studies of Sebelas Maret University organized training for ECEteachers in Sukoharjo and Klaten on how to implement the Curriculum 2013. This training provided anexample of scientific approach based-activities and method to do recording of authentic assessment. It aimedto train teachers to be able immediately put it into practice in the classroom. Results from the training areteachers have increased their competences in the preparation of learning tools, scientific approach basedactivities,anddoauthenticassessmentprocess.